The Effect of Pre-Treatment Depression, Anxiety and Somatization Levels on Transforaminal Epidural Steroid Injection: A Prospective Observational Study - (:unkn) unknown (AM SOC INTERVENTIONAL PAIN PHYSICIANS, 2020)
Background: Results of the lumbar transforaminal epidural steroid injection (L-TFESI) used in the treatment of lumbar radiculopathy may be affected by the current psychiatric condition of the patient. Objectives: The study aimed to assess the effects of pretreatment comorbid psychiatric conditions on patient outcomes in patients with lumbar disc herniation and radiculopathy. Study Design: The study used a prospective-observational study design. Setting: Research was conducted at a university hospital international pain management center. Methods: In this observational study, 103 patients were included. All patients were evaluated with the Hospital Anxiety and Depression scale (HADS) for depression and anxiety levels and the Somatosensory Amplification Scale (SSAS) for somatization levels before the L-TFESI. The treatment results were evaluated with the Numeric Rating Scale (NRS) and the Oswestry Disability Index (ODI) at baseline, the third week, and the third month. Relative to baseline, a 50% reduction in the NRS was accepted as a successful treatment. Results: HADS-depression, HADS-anxiety, and SSAS levels were similar between the patients with successful treatment outcome and the patients in whom treatment failed. However, there were negative correlations between percent reduction in the NRS and the HADS-depression levels at 3 weeks (r = -0.182, P= .022) and 3 months (r = -0.204, P= .037). Also, there were positive correlations between patients' pre-injection ODI scores and both the HADS-anxiety (r = 0.271, P= .001) and SSAS (r = 0.201, P= .013) scores. Limitations: The study was limited by a relatively short-term follow-up period. Conclusions: Although psychiatric conditions affected the pain and disability of patients before and after the L-TFESI, and may have an impact on patient-related outcomes, they should not be a reason to not treat patients or expect a lower chance of success.
Keywords: Anxiety; depression; disc herniation; low-back pain; lumbar radiculopathy; patient-related outcomes; somatization; transforaminal epidural steroid injection; PATIENT-REPORTED OUTCOMES; RADICULAR PAIN; LUMBAR; INTERLAMINAR; DISKECTOMY; DISABILITY; EFFICACY; QUALITY